Associative memory advantage in grapheme-color synesthetes compared to older, but not young adults - Pfeifer, Gaby; Rothen, Nicolas; Ward, Jamie; Chan, Dennis; Sigala, Natasha (Frontiers in Psychology, 2014)
People with grapheme-colour synaesthesia perceive enriched experiences of colours in response to graphemes (letters, digits). In this study, we examined whether these synaesthetes show a generic associative memory advantage for stimuli that do not elicit a synaesthetic colour. We used a novel between group design (14 young synaesthetes, 14 young and 14 older adults) with a self-paced visual associative learning paradigm and subsequent retrieval (immediate and delayed). Non-synaesthesia inducing, achromatic fractal pair-associates were manipulated in visual similarity (high and low) and corresponded to high and low memory load conditions. The main finding was a learning and retrieval advantage of synaesthetes relative to older, but not to younger, adults. Furthermore the significance testing was supported with effect size measures and power calculations. Differences between synaesthetes and older adults were found during dissimilar pair (high memory load) learning and retrieval at immediate and delayed stages. Moreover, we found a medium size difference between synaesthetes and young adults for similar pair (low memory load) learning. Differences between young and older adults were also observed during associative learning and retrieval, but were of medium effect size coupled with low power. The results show a subtle associative memory advantage in synaesthetes for non-synaesthesia inducing stimuli, which can be detected against older adults. They also indicate that perceptual mechanisms (enhanced in synaesthesia, declining as part of the aging process) can translate into a generic associative memory advantage, and may contribute to associative deficits associated with healthy aging.